2005
DOI: 10.1097/01.ta.0000196002.03681.18
|View full text |Cite
|
Sign up to set email alerts
|

Recovery at One Year Following Isolated Traumatic Brain Injury: A Western Trauma Association Prospective Multicenter Trial

Abstract: Older patients following isolated TBI have poorer functional status at discharge and make less improvement at 1 year compared with all other patients. These worse outcomes occur despite what appears to be less severe TBI as measured by a higher GCS upon admission. Differences in outcome begin to appear even in patients between 45 and 59 years. Further investigations with more detailed outcome instruments are required to better understand the qualitative limitations of a patient's recovery and to devise strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 29 publications
3
64
0
1
Order By: Relevance
“…Confirmed factors of poor prognosis for patients with GCS 3 or 4 and older than 65 years are closed basal cisterns and midline shift > 15 mm on the first CT (Brazinova et al, 2010). The worse outcomes in elderly human subjects occur despite what appears to be less severe TBI, as measured by a higher GCS upon admission (Livingston et al, 2005;Susman et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirmed factors of poor prognosis for patients with GCS 3 or 4 and older than 65 years are closed basal cisterns and midline shift > 15 mm on the first CT (Brazinova et al, 2010). The worse outcomes in elderly human subjects occur despite what appears to be less severe TBI, as measured by a higher GCS upon admission (Livingston et al, 2005;Susman et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, increasing age is strongly associated with a poor prognosis both in experimental trauma models and following TBI in humans (Livingston et al, 2005;Onyszchuk et al, 2008;Rothweiler et al, 1998;Sendroy-Terrill et al, 2010;Susman et al, 2002). Confirmed factors of poor prognosis for patients with GCS 3 or 4 and older than 65 years are closed basal cisterns and midline shift > 15 mm on the first CT (Brazinova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 These findings lend credibility to previous retrospective and shorter-term longitudinal studies suggesting a risk for dementia and continued functional decline (some of it perhaps, due to dementing illness) among older individuals, as longitudinal data were utilized for this investigation. 11,12,[18][19][20] Interestingly, TBI survivors who improved over time were slightly younger (though not significantly), and had worse disability ratings at admission to and discharge from rehabilitation services than patients who did not improve, and therefore had more room for improvement. While this may explain the potential for greater improvement among the young as compared to older patients, actual improvement over time reflected by the DRS is less understood.…”
Section: Discussionmentioning
confidence: 99%
“…54 In that study of 236 patients, the TBI patients above 60 years who were discharged with a Glasgow Outcome Score (GOS) of less than 4 showed lower FIM Scores at 1 year, compared with younger patients. In the clinical trial reported by Temkin et al, 1 no data on GOS (or any other scoring system) upon discharge were reported.…”
Section: Efficacy Studies With Magnesiummentioning
confidence: 96%